أثر التحول الرقمي على الأداء الوظيفي لموظفي إدارة الدراسات العليا بجامعة الزاوية (Comprehensive Journal of Science, 2026)
The study aimed to explore the impact of digital transformation on the job performance of employees in the Graduate Studies Administration at the University of Zawiya. A descriptive‑analytical approach was used, employing a five‑point Likert scale questionnaire administered to all administration staff (N = 53). Data were analyzed using SPSS version 26. Cronbach’s alpha indicated good reliability (α = 0.665–0.870). All dimension means exceeded the neutral value of 3 and were statistically significant (p
Keywords: Digital Transformation, Job Performance, Technical Infrastructure, Operational Efficiency, Training and Development